Single and three phase circuits - Mychael, Arthur (South Melbourne : Nelson, 1995)
This book is divided into eight parts: Impedance and Phasor Diagrams; Resonance; AC Power; Power Factor; Power Factor Correction; Three-Phase Theory-Balanced Conditions; Three-Phase Theory-Unbalanced Conditions; Three-Phase Power.
Keywords: Electric circuits; Alternating current; Electric circuits -- Alternating current; Electronic circuits